Impacto das exportações no crescimento econômico: análise do caso brasileiro - Machado, Keli Prezzotto (2017)
The causes of economic growth, as well as the need for international trade between countries, have long been discussed. The factors that aid growth have changed according to each economic school. Economic growth is considered to be measured through GDP, so some jobs use exports as a possible source of consistent growth in the long run. In this sense, it was proposed to verify the role played by exports in terms of the acceleration of Brazilian economic growth? In order to answer this question, this study aims to analyze whether exports are preponderant to the economic growth of Brazil in the period from 1975 to 2017. For this purpose, we will use the Export-led-growth (ELG) hypothesis, which Exports boosts economic growth. Using time series data of the GDP and exports variables, the adopted econometric procedures were the unit root test to test the stationarity, Johansen cointegration test to verify the existence of cointegration between the variables, and the Granger causality test to verify The causality. The main results suggest the absence of cointegration and the bias of the variables for the analysis period.